Vajdaság az európai területi együttműködésben : a Duna Stratégia - Fejes, Zsuzsanna (Közép-Európai Közlemények, 2011)
The aim of the study is to present the position and possibilities of Vojvodina in the European territorial cooperation with special focus on the EU Strategy for the Danube Region. Firstly, I examine the external relations of Vojvodina. I analyse the institutionalisation and the future of the DKMT Euroregion and the Banat-Triplex Confinium EGTC from the aspect Vojvodina, because these cooperations are significant component of the European integration process. The European territorial cohesion includes all the cross-border, transnational and interregional cooperations and democratic local and regional structures, forming under the identity of the EU Danube Strategy. This macro-regional strategy covers parts of 8 EU countries and 6 non EU countries (include Serbia) and faces numerous specific challenges: big socioeconomic disparities, underdeveloped potential of the Danube waterway, a unique environment threatened by pollution –to name just a few. Accordingly, there is a need for a stronger than usual cooperation dimension and for an integrated cooperative response across borders. Finally, I summarise how the Danube Strategy can achieve greater effect and reveal how macro-regional cooperation can help tackle local problems in Vojvodina, providing alternative solutions to problems stemming from legal and institutional differences of the border regions.